Implementation Of Digital Media Agumented Reality Based On Integrated Neuroscience Of The Qur'an To Improve Students' Physical Insight And Spiritual Attitudes In The Era Of Society 5.0 - Lailatul Nuraini; Jalis Syarifah; Halimatus Sa’diyah; Moh Kelvin; M. Athar (FKIP, Universitas Palangka Raya, 2024)
Technological developments in the 21st century have had a significant impact on various fields, including education. This study examines the effectiveness of the use of Augmented Reality (AR)-based learning media integrated with neuroscience and Qur'anic values in improving students' understanding of physics and spiritual attitudes in the Society 5.0 era. The research was conducted in two Islamic-based schools, namely SMA Darussalam Blokagung and MA Al-Amiriyyah Blokagung, using quantitative methods with pre-test and post-test. The results showed that AR learning media significantly improved students' understanding of physics concepts and spiritual attitudes, as evidenced by the difference in pre-test and post-test scores as well as the results of the N-Gain test which showed the effective category, with an average N-Gain score of 77.12% at SMA Darussalam Blokagung and 76.05% at MA Al-Amiriyyah Blokagung. In addition, students' spiritual attitudes also increased with the average questionnaire score showing the category of